The Absolute Reflectance and New Calibration Site of the Moon - Wu, Yunzhao; Wang, Zhenchao; Cai, Wei; Lu, Yu (The Astronomical journal, 2018)
How bright the Moon is forms a simple but fundamental and important question. Although numerous efforts have been made to answer this question such as use of sophisticated electro-optical measurements and suggestions for calibration sites, the answer is still debated. An in situ measurement with a calibration panel on the surface of the Moon is crucial for obtaining the accurate absolute reflectance and resolving the debate. China's Chang'E-3 (CE-3) "Yutu" rover accomplished this type of measurement using the Visible-Near Infrared Spectrometer (VNIS). The measurements of the VNIS, which were at large emission and phase angles, complement existing measurements for the range of photometric geometry. The in situ reflectance shows that the CE-3 landing site is very dark with an average reflectance of 3.86% in the visible bands. The results are compared with recent mission instruments: the Lunar Reconnaissance Orbiter Camera (LROC) Wide Angle Camera (WAC), the Spectral Profiler (SP) on board the SELENE, the Moon Mineralogy Mapper (M3) on board the Chandrayaan-1, and the Chang'E-1 Interference Imaging Spectrometer (IIM). The differences in the measurements of these instruments are very large and indicate inherent differences in their absolute calibration. The M3 and IIM measurements are smaller than LROC WAC and SP, and the VNIS measurement falls between these two pairs. When using the Moon as a radiance source for the on-orbit calibration of spacecraft instruments, one should be cautious about the data. We propose that the CE-3 landing site, a young and homogeneous surface, should serve as the new calibration site.